Claim For Compensation of Utilizing E-Mail Personal Data Under Act No. 19 Year 2016 About the Electronic Transaction and Information - Zulfa Ul Hazanah; Putu Ari Sara Deviyanti; Descamvri Intan Zams Pettalolo; Merlyn Lucia; Terecia Wenas (Hang Tuah Law Journal, 2018)
Personal data in electronic mail needs to be protected. Any collection and dissemination of personal data is classified into violation against individual’s privacy, as personal right involves the rights of determining, providing, or not providing personal data. Private data is a high-valued economy asset or commodity. This far, however, the protection on individual’s personal data in Indonesia is not set under a specific regulation, and thus evoking various issues against private right, in particular to personal data. The personal data discussed in this study is related to electronic one, especially electronic mail, and this refers to Act No. 19 Year 2016 about the Amendment of Act No. 11 Year 2008 about Electronic Transaction and Information. Nevertheless, it solely has restricted regulation on personal data, while the issue of utilizing individual’s personal data is increasing. This paper discusses the concept of personal data in terms of electronic mail along with the regulation of its utilization. The result shows that the concept of personal data in electronic mail is specifically extensive, involving the scope of private information and communication.